2022
DOI: 10.1108/jhtt-07-2021-0209
|View full text |Cite
|
Sign up to set email alerts
|

Gains-focused vs risk-averse orientations and their impact on location-based marketing services in tourism

Abstract: Purpose Regulatory focus theory proposes that people make decisions and engage in the pursuit of goals based on either promotional goals indicating sensitivity to gains/nongains or preventional goals reflecting sensitivity to losses/nonlosses (Aaker and Lee, 2001). The purpose of this study is to examine the roles of regulatory foci and their impact on the perceived value and usage of location-based services (LBS) in travel experiences. Design/methodology/approach Travel planning strategies are framed along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Ordering Systems Digital Customers can use digital ordering systems, such as ScanDine, to place orders by using their cellphones to scan QR codes or open restaurant apps. Prior research has demonstrated the advantages of these systems in improving operational effectiveness and customer experience (Beldona et al, 2018). Digital menus and ordering platforms, according to Lee et al (2019), minimize errors related to human order taking and cut down on wait times, increasing consumer satisfaction.…”
Section: IImentioning
confidence: 99%
“…Ordering Systems Digital Customers can use digital ordering systems, such as ScanDine, to place orders by using their cellphones to scan QR codes or open restaurant apps. Prior research has demonstrated the advantages of these systems in improving operational effectiveness and customer experience (Beldona et al, 2018). Digital menus and ordering platforms, according to Lee et al (2019), minimize errors related to human order taking and cut down on wait times, increasing consumer satisfaction.…”
Section: IImentioning
confidence: 99%
“…The regulatory focus theory has previously been used to explain how marketing communications can affect an individual’s decision-making (Petersen et al , 2015), such as to better understand government communications (Utych, 2021), crisis perceptions (Avnet and Laufer, 2015) and crisis attitudes and responses (Stam et al , 2018). Pertinent to this enquiry, the regulatory focus theory has a prevalence in tourism and hospitality scenarios, including location-based tourism marketing services (Beldona et al , 2022), reaction and coping with travel constraints (Jian et al , 2021) and tourism seasonality (Senbeto and Hon, 2019). It seems reasonable, therefore, that the regulatory focus theory will assist in uncovering whether prevention or promotion-focused messages are meaningful for designing a crisis-oriented internal communication strategy.…”
Section: Literature Reviewmentioning
confidence: 99%